ChemoImmunoModulation: immune regulation by the antineoplastic chemotherapeutic agents - Shurin, Michael R.; Umansky, Viktor (Current medicinal chemistry, 2012)
Since 1948, when Farber et al. introduced aminopterin, the first chemotherapeutic agent, more than 100 such agents have come into use. Initially, antitumor...